Female College Athletes and Osteoporosis: Strategies for Prevention and Treatment - Turner, Lori W.; Wang., Min Q.; Schade, Debra H.; Pulley, LeaVonne; Westerfield, R. Carl (My University, 1996)
For some female athletes, a risk exists for the development of one or more of the medical disorders that comprise the female athlete triad: the related conditions of disordered eating, amenorrhea, and osteoporosis. These disorders may lead to significant morbidity and a high rate of mortality. The female college athlete, driven to excel in her sport and pressured to fit a thin athletic image, is at risk for the development of premature osteoporosis. College counselors and advisors can be instrumental in the prevention and treatment of these problems in female college athletes.
Keywords: health; sex/gender